Masticatory dysfunction is associated with osteoporosis in older men - Alice Laudisio
Aim: Thirty per cent of hip fractures occur in men. Nevertheless, the determinants of osteoporosis in men are unclear. Masticatory dysfunction is associated with malnutrition, and might represent an emergent cause of osteoporosis. The aim of this study was to assess the association of bone mineral density and self-assessed masticatory dysfunction in a general older population. Material and Methods: We assessed the association of masticatory dysfunction with standard parameters of bone mineral density (T-score, Z-score and the stiffness index) in all 310 subjects aged 751 living in Tuscania (Italy). Results: Among men, self-assessed masticatory dysfunction was associated with T-score [b50.86, confidence intervals (CI)50.15–1.57; p50.019], Z-score (b50.86, CI50.16–1.56; p50.017) and the stiffness index (b59.12, CI50.47–17.77; p50.039) in linear regression modeling, after adjusting. No significant associations were observed in women. Conclusions: Masticatory dysfunction is independently associated with osteoporosis in elderly men. Evaluation of masticatory function should enter the routine assessment of older men with osteoporosis.